Special education practice : applying the knowledge, affirming the values, and creating the future (Brooks/Cole, 1997)
This book is divided into five parts: Special education policy challenges in the year 2000 and beyond; School practices; Families and community services; Teacher education; Some of the challenges in creating the future.